Colonial emulation: sinophobia, ethnic stereotypes and imperial anxieties in late eighteenth-century economic thought. Issue 8 (17th November 2017) - Smith, Blake
ABSTRACT: In 1799 Dirk van Hogendorp published a Report on the Current Conditions of Dutch Possessions in the East Indies, a document that has garned comparisons to Adam Smith's Wealth of Nations (1776) for its condemnation of the Dutch East India Company and for its insistence on the importance of property rights to economic growth. The text is also an anti-Chinese diatribe, castigating the supposedly inveterate avarice of Java's Chinese minority. Hogendorp's advocacy of colonial reform and sinophobia intertwine in his use of the term ijver, then the standard Dutch translation of 'emulation', a keyword of eighteenth-century political economy. Read against the status of emulation in European thinking, Hogendorp's employment of the ijver offers an opportunity to re-examine emulation's fraught, ambivalent quality, which has been noted by scholars like Istvan Hont and Sophus Reinert concerned primarily with a division between benevolent domestic emulation and dangerous international emulation. The colonial sphere, neither wholly domestic nor wholly foreign, was a discursive site wherein the tensions of emulation were worked out in new ways.